Strength of Reinforced Concrete Columns with Transverse Openings - Ihsan A.S. AL-Shaarbaf, Ass. Prof. Dr.; Abbas AbdulMajeed Allawi, Ass. Prof. Dr.; Nabeel H. AlSalim, Lecturer (Journal of Engineering, 2017)
The present work is concerned with the investigation of the behavior and ultimate capacity of axially loaded reinforced concrete columns in presence of transverse openings under axial load plus uniaxial bending. The experimental program includes testing of twenty reinforced concrete columns (150 × 150 × 700 mm) under concentric and eccentric load. Parameters considered include opening size, load eccentricity and influence of the direction of load eccentricity with respect to the longitudinal axis of the opening. Experimental results are discussed based on load – lateral mid height deflection curves, load – longitudinal shortening behavior, ultimate load and failure modes. It is found that when the direction of load eccentricity is parallel to the longitudinal axis of openings, column behavior is more pronounced when than the direction is normal to the longitudinal axis of openings.